ID 285 – Involvement of A-beta sensory fibres in amyotrophic lateral sclerosis. Issue 3 (March 2016) - Isak, B.; Tankisi, H.; Johnsen, B.; Pugdahl, K.; Brix Finnerup, N.; Torvin Møller, A.; Brøgger Christensen, P.; Fuglsang-Frederiksen, A.
Abstract : Background: Detection of any sensory abnormality in nerve conduction studies (NCSs) usually leads the physician to exclude amyotrophic lateral sclerosis (ALS). However, increasing evidence suggested that ALS is a multisystem disorder that also involves the sensory nerves. Objective: In this study we wanted to see if proximal and distal large diameter sensory nerves were deteriorated in ALS. Methods: 15 definite-ALS patients and 27 healthy subjects were evaluated based on distal sensory NCSs [i.e., antidromic dorsal sural (DS) and orthodromic medial plantar (MP)] in addition to standardized proximal sensory NCSs [i.e., unilateral median sensory and bilateral sural (SU) nerves]. Also, somatosensory evoked potentials (SEPs) in upper (UE-) and lower extremities (LE-) were recorded. Results: ALS patients had abnormal DS-NCSs (9 patients bilaterally and 3 patients unilaterally) and MP-NCSs (6 patients bilaterally and 1 patient unilaterally) while median sensory- and right SU-NCS were abnormal in 1 and 4 patients, respectively. Also, UE- and LE-SEPs were abnormal in 5 and 7 patients, respectively. Conclusions: Distal sensory NCSs probably deteriorate earlier and more than proximal sensory NCSs in ALS. Key message: A-beta sensory fibers are involved as well as corticospinal fibers in ALS.